ANALISIS PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN DI HOTEL BANGKA CITY PANGKALPINANG - Agustin, Sella; Lestari, Deara Shinta; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2023)
The purpose of this study was to determine the effect of service quality, customer relationship management and customer satisfaction on customer loyalty, either simultaneously or partially. This research was conducted from January 2023 to June 2023. The theory used in this research is the theory of Management, Marketing Management, Service Quality, Price Perception, Location and Customer Satisfaction. The method used in this research is descriptive with a quantitative approach with a view to finding the relationship between the independent variables (service quality, price perception, location) and the dependent variable (customer satisfaction) using statistical formulas. While the statistical formula used to test the hypothesis is Multiple Linear Regression Analysis. The sample in this study amounted to 100 people. The service quality variable (X1) where tcount (3.962) > ttable (1.660) means that the service quality variable (X1) has a partial effect on customer satisfaction (Y). The price perception variable (X2) where tcount (2.675) > ttable (1.660) means that the price perception variable (X2) has a partial effect on customer satisfaction (Y). The location variable (X3) where tcount (1.992) > ttable (1.660) means that the location variable (X3) has a partial effect on customer satisfaction (Y). The results of the F test show that the comparison of Fcount 68.403> Ftable 2.70, it can be concluded that the variables of service quality(X1), price perception (X2) and location (X3) have a simultaneous effect on customer satisfaction (Y).